2008
DOI: 10.1038/ajh.2008.249
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Effects of Statins May Improve Outcomes in Atherosclerotic Renovascular Disease

Abstract: Statin therapy was associated with lesser rate of progression of renal insufficiency (with 7.4% of S patients reaching renal end points vs. 38.9% of NS patients) and lower overall mortality (5.9 % in S vs. 36.1% in NS patients), P < 0.001 for both. Although both groups received what was deemed optimal therapy, they did have other differences that may have affected the outcomes (a limitation addressed by Cox multiple regression analysis). These results suggest the need for prospective randomized controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…6 In this 11-year long retrospective observational study, the authors confirm former reports identifying renal dysfunction due to ARAS as a predictor of cardiovascular mortality. As a novel finding, Silva et al identified the use of statins as beneficial regarding renal function preservation (progression of renal insufficiency: 7.4% of S patients (patients who received statin therapy) vs. 38.9% of NS patients (patients who had no statin)) and patient survival (overall mortality: 5.9% in S patients vs. 36.1% in NS patients).…”
supporting
confidence: 85%
“…6 In this 11-year long retrospective observational study, the authors confirm former reports identifying renal dysfunction due to ARAS as a predictor of cardiovascular mortality. As a novel finding, Silva et al identified the use of statins as beneficial regarding renal function preservation (progression of renal insufficiency: 7.4% of S patients (patients who received statin therapy) vs. 38.9% of NS patients (patients who had no statin)) and patient survival (overall mortality: 5.9% in S patients vs. 36.1% in NS patients).…”
supporting
confidence: 85%
“…statins are safe and effective in preventing cardiovascular events in patients with chronic kidney disease before dialysis, including patients with atherosclerotic ras. 16,34,35 renin-angiotensin antagonists are more effective than other antihypertensive agents in reducing blood pressure and preventing death in animal models of ras. 36 with the exception of one inconclusive trial that included only six patients 37 and another that was poorly designed, 38 no randomized, controlled trials have been carried out to compare standard treatment with renin-angiotensin antagonists in patients with ras.…”
Section: Diagnosismentioning
confidence: 99%
“…Statins (HMG CoA reductase inhibitors) have well established beneficial effects in reducing cardiovascular risk, and statin treatment is clearly indicated in CVD guidelines [1-3]. More specifically, statins significantly decrease low-density lipoprotein cholesterol (LDL-C) and beneficially affect outcomes (including cardiovascular mortality, all-cause mortality, cardiovascular events, and revascularization) in different patient groups; these effects have been reviewed extensively recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, patients do not always adhere to their medication, and statin compliance is low in clinical practice.…”
Section: Introductionmentioning
confidence: 99%